Atomoxetine may improve methylphenidates efficacy in tretment of ADHD? - Niederhofer, Helmut (Array, 2009)
The reported case mainly shows that the combination between atomoxetine and methylphenidate helped reducing the dose of methylphenidate and thus, probably the side effects while showing beneficial clinical effects. Further systematic research should be done to investigate this observation